UJI FITOKIMIA, TOKSISITAS DAN AKTIVITAS ANTIOKSIDAN ALAMI DAUN TUMBUHAN KELAKAI (Stenochlaena palustris) DENGAN METODE DPPH - Bonita Tahir; Chairul Saleh; Subur P Pasaribu (PROSIDING SEMINAR KIMIA, 2013)
The phytochemical test, brine shrimp lethality test and activity antioxidant test and secondary metabolits of kelakai(Stenochlaena Palustris) leaves have been researched. The leaves samples are extract with solvent methanol by masseration method and that is concentrated by using rotary evaporator. The methanol crude extract obtained are fractioned with solvent n-hexane and. Solvent ethyl acetat.Based on secondary metabolits phytochemical test of kelakai leaves showed that methanol raw extract contains steroid, alkaloid and flavonooid. n-hexane fraction extract contains steroid and alkaloid Ethyl acetat fraction extract contains alkaloid, steroid, flavonoid and saponin.In brine shrimp lethality test, the increase larvae death and data was yielded recorded and processed using SAS Probit Analysis to determine the lethal concentration 50 % (LC 50 ) value. The results of this test obtained data and showed that the most active fraction is ethyl acetat fraction extract withvalue of LC 50 was equel to 88,8477 ppm.Based on the antioxidant activity conducted by scavenging activity of DPPH usedspectrophotometry. Based on the result be held researched was obtained that Inhibition Concentration 50% (IC 50 ) that methanol raw extract value of 185,92 ppm, n-hexane fraction value of 520,64 ppm and athyl acetat fraction 107,49 ppm and vitamin C is value of 3,064 ppm, can be axpressed that the result of this test showed that the most active fraction is ethyl acetat with value of IC 50 equel to 107,49 ppm.